2001
DOI: 10.1212/wnl.57.7.1248
|View full text |Cite
|
Sign up to set email alerts
|

Axonal loss in normal-appearing white matter in a patient with acute MS

Abstract: These studies confirm axonal degeneration in the absence of myelin loss as one histopathologic correlate to abnormal MR findings in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
150
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(162 citation statements)
references
References 28 publications
7
150
0
5
Order By: Relevance
“…A decrease in absolute concentration of these metabolites reflects loss of neurons in the course of illness, either reversible or persistent. 33 Interestingly, we also found significantly lower tNA concentrations in patients with SPMS compared with those with RRMS, consistent with a progression in the course of the disease. In the work by Pouwels and Frahm, 24 it was shown that there are more pronounced differences in regional intrasubject concentrations of tNA than of NAA alone, comparing frontal, parietal, and occipital white matter.…”
Section: Discussionsupporting
confidence: 79%
“…A decrease in absolute concentration of these metabolites reflects loss of neurons in the course of illness, either reversible or persistent. 33 Interestingly, we also found significantly lower tNA concentrations in patients with SPMS compared with those with RRMS, consistent with a progression in the course of the disease. In the work by Pouwels and Frahm, 24 it was shown that there are more pronounced differences in regional intrasubject concentrations of tNA than of NAA alone, comparing frontal, parietal, and occipital white matter.…”
Section: Discussionsupporting
confidence: 79%
“…Accordingly, by boosting a well controlled immunity that simulates or cross-reacts with weak selfreacting T cells, it is possible to counteract the destructive effect of self-compounds such as glutamate (15,19,43). Recent evidence suggests that elements of neurodegenerative and autoimmune disorders can be intermingled in the same disease Processes known to occur in degenerative diseases have been detected in autoimmune diseases (20,(44)(45)(46)(47)(48). It is thus possible that in ''mixed'' disorders the degenerative tissue will benefit from immunomodulation rather than from immunosuppression (43).…”
Section: Discussionmentioning
confidence: 99%
“…This empty myelin, axonal degeneration in the absence of myelin loss, was similar to empty myelin profiles in NAWM in MS described by Bjartmar and colleagues. 40 …”
Section: Axonal Injury In the Absence Of Vigorous Inflammation Duringmentioning
confidence: 99%